Perceiving the Livable City: Cross-Cultural Lessons on Virtual and Field Experiences of Urban Environments. Issue 3 (2nd October 2018) - Ruggeri, Deni; Harvey, Chester; Bosselmann, Peter
Abstract : Problem, research strategy, and findings: Livability is a popular goal, yet a consistent definition and approach for measuring livability remain elusive. Many urban designers embrace etic indicators such as block size, multimodality, and accessibility rather than emic perceptions of users. Kevin Lynch showed great concern for emic livability and studied how culture and technology might affect it. We examine relationships between emic and etic interpretations of livability, drawing on a pilot study involving both in-person and Google Street View audits performed by U.S. and Norwegian student volunteers in San Francisco (CA) and Oslo (Norway) neighborhoods. Audits recorded both etic and emic measurements of walkability, compactness, connectivity, enclosure, and imageability, commonly associated with livable urban environments. Results show substantial differences between emic and etic measures. Regression models show that of all etic variables, only a few are useful predictors of emic measures. Country of origin also has no significant effect in these models, which suggests that emic interpretations of livability are reasonably consistent among auditors from both nations despite their lack of previous familiarity with non-home cities. Takeaway for practice: Emic impressions of livability may be more internationally transferable than etic qualities traditionally associated with livable places. Google Street View led to greater livability impressions than in-person audits, which suggests caution in relying on virtual experiences as proxies for fieldwork.